Survey and analysis of tooth extraction anxiety of dental patients - Cui, Qing-Ying; Chen, Si-Yu; Fu, Shuai; Zhang, Chang-Bin; Li, Ming (Hua xi kou qiang yi xue za zhi = Huaxi kouqiang yixue zazhi = West China journal of stomatology, 2018)
This study aims to understand the current status and analyze the influencing factors of tooth extraction anxiety of dental patients. The General Factor Questionnaire and Modified Dental Anxiety Scale (MDAS) were used to survey and analyze tooth extraction anxiety of 800 dental patients. Single-factor and multi-factor analyses were used for statistical data analysis. A total of 768 qualified questionnaires were received out of 800, the efficiency was 96%. The mean MDAS score was 10.21±3.29. The prevalence percentage of dental anxiety was 14.7%. Significant statistical differences of the incidence of dental anxiety were observed with regard to sex, age, tooth extraction time, accompanying relatives and friends, before tooth extraction, tooth extraction experience for family and friends, pain tolerance, mental health state before tooth extraction, and self-reported oral health status (P<0.05. By contrast, no significant statistical differences in the incidence of dental anxiety were observed with regard to educa